Školska učinkovitost i obrazovni menadžment: ususret smjernicama istraživanja i javne politike u Jugoistočnoj Europi (Morepress Books, 2025)
This university book is intended to support the professionalization of school principals as key leaders in the educational process. It is the result of the project "Principal: Profession and Qualification, Not Just a Function," co-financed by the European Social Fund. The book offers a comprehensive overview of the specific roles and responsibilities of school principals within the field of educational management. Principals are expected to navigate and balance the demands of both local communities and national educational policies, while efficiently managing school resources and providing visionary leadership. Such a balanced and democratic approach to school leadership requires a deep understanding of the complex political, economic, social, and technological contexts in which various stakeholders in the educational system operate. In response to these challenges, the book explores the conceptual, methodological, and empirical foundations of school effectiveness and educational leadership. Key topics include the management and leadership roles of principals, strategies for effective school governance, and approaches to communication and collaboration with the broader community and local stakeholders.